2020
DOI: 10.7759/cureus.7149
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl Cysteine Use in the Treatment of Shock Liver

Abstract: Acute liver failure is a rare, life-threatening illness accounting for about 7% of all liver-related deaths. Patients with acute liver failure are managed with supportive care initially, and if supportive care fails, liver transplantation is the definitive option for eligible candidates in liver failure. N-acetyl cysteine (NAC) has a well-established role in acetaminophen-induced liver failure and has been reported to reduce mortality in these patients. It has also been reported to provide benefit in non-aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Parvataneni et al employed NAC in shock liver, contrary to the belief that NAC should not be used for shock or ischemic hepatitis. They observed positive results, and the use of NAC helped prevent the need for liver transplant [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parvataneni et al employed NAC in shock liver, contrary to the belief that NAC should not be used for shock or ischemic hepatitis. They observed positive results, and the use of NAC helped prevent the need for liver transplant [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it promotes an increase in nitrite levels, leading to vasodilation, thereby enhancing oxygen delivery to tissues. [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis showed that reduced expression of NQO1, GSTP1, GSTA5, GSTM1, AKR7A1, and GCLC may also lead to decrease the level of N-acetyl-L-cysteine (NAC). NAC is GSH precursor, which increases its concentration, elevates NO levels, and provides overall anti-inflammatory activity [ 103 ]. In the study conducted by Sueck et al, the conjugated OTA-NAC metabolite was observed in human urine [ 104 ].…”
Section: The Mechanisms Responsible For Liver Damagementioning
confidence: 99%